Wastewater Surveillance Detected Carbapenemase Enzymes in Clinically Relevant Gram-Negative Bacteria in Helsinki, Finland; 2011–2012 - Tiwari, Ananda; Paakkanen, Jaana; Österblad, Monica; Kirveskari, Juha; Hendriksen, Rene S.; Heikinheimo, Annamari (Frontiers in Microbiology, 2022)
Antimicrobial resistance profiling of pathogens helps in identifying the emergence of rare or new resistance threats and prioritizing possible actions to be taken against these threats. The analysis of wastewater (WW) can reveal the possible circulation of antimicrobial-resistant bacteria (ARB) and antimicrobial resistance genes (ARG) in the catchment communities. Here we analyzed WW influent samples to determine the prevalence of carbapenemase genes carrying Gram-negative bacteria (Carba-GNB) in Helsinki, Finland. This study highlights a pioneering study that set important historical reference points from the very early stage of the carbapenemase era, during the period 2011-2012. A total of 405 bacterial isolates grown on CHROMagarKPC (n=195) and CHROMagarESBL (n= 210) from WW influent samples were collected between October 2011 and August 2012 and were analyzed. The bacterial DNA from the isolates was extracted, and the prevalence of carbapenemases genes blaKPC, blaNDM, blaGES, blaOXA-48, blaIMP, blaIMI, and blaVIM were screened with multiplexed quantitative real-time PCR. All carbapenemase-positive isolates were identified with matrix-assisted laser desorption ionization-time of flight mass spectrometry (MALDI-TOF MS). The nucleic acid extraction was successful for 399 isolates, of which 59 (14.8%) were found to carry carbapenemase genes. A total of 89.8% of the carbapenemase positive isolates (53 out of 59) were obtained from CHROMagarKPC plates and only 10.2% (6 out of 59) were obtained from CHROMagar ESBL plates. Among the Carba-GNB isolates, 86.4% were blaGES (51 out of 59), 10.2% were blaKPC (6 out of 59), and 3.4% were blaVIM (2 out of 59). The most common carba-gene, blaGES, was carried by ten different bacterial species, such as Aeromonas spp., Enterobacter spp., and Kluyvera spp.; the blaKPC gene was carried by Escherichia coli, Klebsiella pneumoniae, and Kluyvera cryocescens; and the blaVIM gene was carried by Aeromonas hydrophila/caviae and Citrobacter amalonaticus. This study suggests that wastewater surveillance could be a potential tool for monitoring AMR in the population.